Greater Acute Concussion Symptoms Are Associated With Longer Recovery Times in NCAA Division III Collegiate Athletes - Iverson, Grant L.; Terry, Douglas P.; Maxwell, Bruce; Zafonte, Ross; Berkner, Paul D.; Cook, Nathan E. (Frontiers in Neurology, 2022)
We examined the association between the severity of acute concussion symptoms and time to return to school and to sports in National Collegiate Athletic Association (NCAA) Division III collegiate athletes. We hypothesized that students with the lowest burden of acute symptoms, measured in the first 72 h, would have the fastest return to school and sports and those with the highest burden of symptoms would have the slowest return to school and sports. This injury surveillance cohort included 808 athletes from 11 NCAA Division III colleges who sustained a concussion between 2014 and 2019. Athletic trainers documented time to return to school and to sports. Kruskal-Wallis tests with post-hoc planned comparison Mann-Whitney U tests were used to assess whether athletes took longer to return based on their acute symptom burden (Low, Medium, or High). Survival analysis (Kaplan Meier with log rank tests) was used to compare the recovery times based on acute symptom burden (censored at 28 days). Chi-square tests compared the proportion of those who had not yet returned to school or sports at various recovery benchmarks (i.e., 1 week, 10 days, 2 weeks, 3 weeks, 4 weeks) based on acute symptom burden. Women (median = 5 days) took slightly longer than men (median = 4 days) to return to school (p = 0.001; r = −0.11, small effect). Women and men did not differ on time to return to sports (p = 0.32, r = −0.04). A greater proportion with high acute symptoms remained out of school at 5 (odds ratio, OR = 4.53), 7 (OR = 4.98), and 10 (OR = 4.80) days compared to those with low acute symptoms. A greater proportion with high acute symptoms remained out of sports at 10 (OR = 4.11), 14 (OR = 3.46), and 21 (OR = 3.01) days compared to those with low acute symptoms. This study shows a strong association between having a high burden of acute post-concussion symptoms and having a slower return to school and sports in Division III collegiate athletes. Moreover, it also illustrates the converse: that those athletes with a low burden of acute symptoms have a faster return to school and sports.